Notalgia Paresthetica Dermatologist Report of Symptom Burden and Treatment: Results from a Physician Survey - Brian S. Kim; Sonja Ständer; Kenji Kabashima; Jennifer A. Mohawk; Sherri So; Joana Goncalves; Nilam Shah; Catherine Munera; Joseph C. Punzalan; Romelia Argudo; Mark Lebwohl (Medical Journals Sweden, 2024)
Notalgia paresthetica (NP) is a sensory neuropathy characterized by chronic pruritus, skin pain, and other pathologic sensations affecting the mid-to-upper back. NP may be under-recognized and under-diagnosed, with limited data available on its symptom presentation and treatment patterns. NP-DERM was an internet-based survey of dermatologists (n = 650) from 8 different countries on their perspectives on NP symptoms and current treatment practices. Dermatologists typically treated a median of 12 patients with NP per month. Dermatologists reported that itch (pruritus) was the most common symptom for their patients with NP, followed by hyperpigmentation and sensitive skin. The most burdensome NP symptom was pruritus, followed by burning or hot sensation, and painful or raw skin. The most prescribed treatments included non-medicated skin care, topical corticosteroids, oral antihistamines, medicated topicals, and gabapentin or pregabalin. Physicians reported low satisfaction with available treatments. The most common reason for physicians to discontinue patients' therapy was lack of response.